Ischemic Stroke in Disguise an Abnormal Movement Ischemic Stroke Case Report - Gabriella; Pratama Wijaya, Ferrdy; Ibonita, Rizka (Acta Neurologica Indonesia, 2026)
Introduction: This case report aims to heighten awareness that acute, sudden-onset abnormal movements can signal an underrecognized ischemic stroke, even without classic BEFAST (Balance, Eyes, Face, Arms, Speech) symptoms. Swift stroke diagnosis is vital, as time critically influences prognosis; yet, the typical presentation of hemiparesis often overshadows atypical features such as movement disorders, risking misdiagnosis. Case Report: A 60-year-old woman presented to the emergency department with sudden abnormal jaw and left limb movements lasting one day, with no prior episodes or accompanying symptoms. Comprehensive physical exams, ancillary tests, and imaging revealed an ischemic stroke in the left corona radiata on MRI (Magnetic Resonance Imaging). Discussion: These hyperkinetic movements stemmed from stroke infarction at corticostriatal fibers region, which normally transmit excitatory glutamatergic signals from the cortex to basal ganglia structures like the caudate nucleus and putamen. This input inhibits the globus pallidus internus, disinhibiting the thalamus to enable smooth movement initiation. Lesions in this pathway, as seen here, provoke abnormal hyperkinetic disorders. Conclusion: Left corona radiata ischemia atypically manifested as isolated movement abnormalities due to corticostriatal pathway interruption. Clinicians must vigilantly consider ischemic stroke in patients with abrupt-onset movement disorders, regardless of the absence of traditional symptoms, to ensure timely intervention and better outcomes.